Coal ash and gangue conglutination material for coal mine and preparation method of coal ash and gangue conglutination material
Through the preparation method of modified fly ash, a three-dimensional network structure is formed to wrap and fix heavy metal ions, which solves the problem of heavy metal ion pollution in traditional fly ash gangue glue solid materials, and achieves higher compressive strength and heavy metal curing performance.
Patent Information
- Application Number
- CN202411891137.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Heavy metal ions in traditional fly ash gangue glue solid material flow into the soil with water, resulting in environmental pollution.
The preparation method of modified fly ash is adopted, including decomposing, hydroxylation, alkenylation of fly ash, and reacting with sodium alginate, polyacrylamide and fluorine chain modified substances at 50°C to form a three-dimensional network structure to wrap and fix heavy metal ions.
It improves the compressive strength of the material and the heavy metal curing ability, reduces the possibility of migration and release of heavy metal ions, and effectively prevents environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mine filling, in particular to a fly ash gangue cement solid for coal mines and a preparation method thereof. Background Art
[0002] Coal resources are the main energy source in my country, providing strong support for the development of our national economy and social stability. This will not change at present or for a considerable period of time in the future.
[0003] As a byproduct of coal mining and washing, the output of coal gangue has increased rapidly with the growth of coal consumption. The accumulation of coal gangue occupies a large amount of land resources, causing serious waste of resources, environmental pollution and other problems.
[0004] Patent technical document CN113321468B discloses a coal gangue cementing filling material and a high-fluidity and high-solid content cementing filling material slurry. The invention discloses a coal gangue cementing filling material and a high-fluidity and high-solid content cementing filling material slurry, wherein the coal gangue cementing filling material is composed of coal gangue, cement, fly ash, auxiliary materials and water reducer; the cementing filling material can obtain good fluidity with less water consumption, and the material has a certain strength after solidification and hardening in the filling area, which can meet the requirements of filling mining and goaf filling for the mechanical properties of filling materials. Patent technical document CN118754517A is a coal gangue backfill functional material and its preparation method. The invention discloses a coal gangue backfill functional material, which includes 800-1200 parts of silt, 50-60 parts of cement, 40-50 parts of fly ash and 1-5 parts of modified polyacrylamide in terms of weight. The coal gangue backfill functional material provided by the invention has excellent flame retardancy, and can also reduce the land occupation of coal gangue accumulation and secondary pollution to the environment, which is conducive to the localization, scale, reduction and ecological utilization of coal gangue. The above patents all provide a fly ash and coal gangue backfill material, but because coal gangue contains heavy metal ions, when used as filling materials, the heavy metal ions contained therein often flow into the soil with water due to the infiltration of groundwater or rainwater, causing pollution to the environment. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a fly ash gangue cement solid for coal mines and a preparation method thereof, so as to solve the problem that heavy metal ions in traditional fly ash gangue cement solids flow into the soil with water, thereby causing environmental pollution.
[0006] Based on the above purpose, the present invention provides a fly ash gangue cement for coal mines, comprising the following raw materials in parts by weight: 50-60 parts of coal gangue, 10-15 parts of cement, 25-35 parts of fly ash, 5-10 parts of modified fly ash, 4-7 parts of activator, and 1-5 parts of water reducer;
[0007] The preparation steps of the modified fly ash are as follows:
[0008] S1: removing impurities from fly ash to obtain pretreated fly ash;
[0009] S2: pretreated fly ash, hydrogen peroxide and concentrated sulfuric acid are mixed, stirred evenly, allowed to stand until the gas is completely released, filtered, washed and dried to obtain hydroxylated fly ash;
[0010] S3: Mix and stir the hydroxylated fly ash and anhydrous ethanol, adjust the pH to 4.5-5, then add silane coupling agent KH-570, react at 90-100° C. for 12-14 hours, filter, wash and dry to obtain olefinated fly ash;
[0011] S4: Sodium alginate is dissolved in deionized water at 50°C, followed by the addition of olefinated fly ash, polyacrylamide, trifluoroethyl acrylate and N,N-methylenebis(acrylamide), and after ultrasonic homogenization, an initiator is added. After reacting at 60-65°C for 3-4h, the fly ash is separated, washed, dried, crushed and sieved to modify the fly ash.
[0012] Preferably, the coal gangue consists of coal gangue fine aggregate and coal gangue coarse aggregate in a weight ratio of 1:1.
[0013] Furthermore, the particle size of the coal gangue fine aggregate is 1-5 mm.
[0014] Furthermore, the particle size of the coal gangue coarse aggregate is 5-15 mm.
[0015] Preferably, the cement is ordinary Portland cement with PO32.5.
[0016] Preferably, the particle size of the fly ash is 10-100 μm.
[0017] Preferably, the activator is a mixture of Na2SiO3, Na2SO4 and NaCl in a weight ratio of 1:2:3.
[0018] Preferably, the water reducer is one of a lignin sulfonate water reducer, a naphthalene-based water reducer, a polycarboxylic acid water reducer, a melamine-based water reducer or an aminosulfonate-based water reducer.
[0019] Preferably, the impurity removal in step S1 is first performed using anhydrous ethanol and then using deionized water.
[0020] Preferably, in step S2, the dosage ratio of the pretreated fly ash, hydrogen peroxide and concentrated sulfuric acid is 40-50g:50-60ml:50-60ml.
[0021] Preferably, the concentration of the hydrogen peroxide in step S2 is 20%.
[0022] Preferably, the concentration of the concentrated sulfuric acid in step S2 is 98%.
[0023] Preferably, the washing in step S2 is washing to neutrality.
[0024] Preferably, in step S3, the weight ratio of the hydroxylated fly ash, the silane coupling agent KH-570 and the anhydrous ethanol is 30-40g:10-15g:300-500g.
[0025] Preferably, the pH adjustment in step S3 is performed using formic acid.
[0026] Preferably, in step S4, the weight ratio of the olefinated fly ash, polyacrylamide, trifluoroethyl acrylate, N,N-methylenebis(acrylamide), sodium alginate, initiator and deionized water is 30-40g:20-25g:1-3g:1-5g:10-15g:0.03-0.05g:200-300g.
[0027] Preferably, the initiator in step S4 is ammonium persulfate.
[0028] Furthermore, the present invention also provides a method for preparing fly ash gangue cement solid for coal mine, comprising the following steps:
[0029] The raw materials are mixed in proportion and stirred evenly to obtain fly ash gangue cement solid for coal mine.
[0030] The beneficial effects of the present invention are as follows: the slurry formed by mixing the fly ash gangue cement for coal mines with water has good fluidity, can meet the requirements of pipeline transportation, and has a short setting time. The filling blocks formed by curing thereof have excellent compressive strength and heavy metal solidification ability.
[0031] The fly ash gangue cement solid for coal mines of the present invention adds sodium alginate during the preparation of modified fly ash, thereby significantly increasing the effective grafting density of polyacrylamide and fluorine chains and forming a three-dimensional network structure on the surface of the fly ash. This structure not only wraps the fly ash particles and the heavy metal ions adsorbed on the surface of the fly ash, but also fills the gaps between the particles, thereby improving the overall density of the material, thereby improving the compressive strength of the filling block and the heavy metal solidification performance.
[0032] The fly ash gangue cement solid for coal mines of the present invention improves the hydrophobicity of the material by using a modified substance with a longer fluorine chain in the process of preparing the modified fly ash, and the long side bonds are entangled with each other, so that the compressive strength of the filling body and the heavy metal solidification performance are improved to a certain extent. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0034] Example 1: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0035] (1) Dispersing fly ash in anhydrous ethanol, stirring evenly, ultrasonically removing impurities for 20 minutes, centrifuging and filtering, dispersing in deionized water, ultrasonically removing impurities for 20 minutes, centrifuging, filtering, and vacuum drying for 12 hours to obtain pretreated fly ash;
[0036] (2) 40 g of pretreated fly ash, 50 ml of hydrogen peroxide (20%) and 50 ml of concentrated sulfuric acid (98%) were mixed and stirred evenly. After the gas was completely released, the mixture was filtered and washed to neutrality, and vacuum dried for 12 h to obtain hydroxylated fly ash;
[0037] (3) Disperse 30 g of hydroxylated fly ash in 300 g of anhydrous ethanol, add formic acid, adjust the pH to 4.5, then add 10 g of KH-570, keep at 90 ° C. for 12 h, filter, wash and dry after the reaction is completed to obtain olefinated fly ash;
[0038] (4) at 50°C, 10 g of sodium alginate is placed in 200 g of deionized water, and after it is completely dissolved, 30 g of olefinized fly ash, 20 g of polyacrylamide, 1 g of trifluoroethyl acrylate and 1 g of N,N-methylenebis(acrylamide) are mixed, and 0.03 g of ammonium persulfate is added, and the mixture is reacted at 60°C for 3 h, separated, and washed with a mixture of water and methanol, and then dried in an oven at 60°C for 30 h, and finally made into powder to obtain modified fly ash;
[0039] (5) Mix 50 g of coal gangue, 10 g of PO3, 25 g of fly ash, 5 g of modified fly ash, 4 g of activator (the weight ratio of Na2SiO3, Na2SO4 and NaCl is 1:2:3), and 1 g of naphthalene-based water reducer, and stir evenly to obtain fly ash gangue cement for coal mines.
[0040] Example 2: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0041] (1) Dispersing fly ash in anhydrous ethanol, stirring evenly, ultrasonically removing impurities for 25 minutes, centrifuging and filtering, dispersing in deionized water, ultrasonically removing impurities for 25 minutes, centrifuging, filtering, and vacuum drying for 20 hours to obtain pretreated fly ash;
[0042] (2) 45 g of pretreated fly ash, 55 ml of hydrogen peroxide (20%) and 55 ml of concentrated sulfuric acid (98%) were mixed and stirred evenly. After the gas was completely released, the mixture was filtered and washed to neutrality, and vacuum dried for 20 h to obtain hydroxylated fly ash.
[0043] (3) Disperse 35 g of hydroxylated fly ash in 400 g of anhydrous ethanol, add formic acid, adjust the pH to 4.7, then add 13 g of KH-570, keep at 95 ° C. for 13 h, filter, wash and dry after the reaction is completed to obtain olefinated fly ash;
[0044] (4) at 50°C, 13g of sodium alginate was placed in 250g of deionized water, and after it was completely dissolved, 35g of olefinized fly ash, 23g of polyacrylamide, 2g of trifluoroethyl acrylate and 2g of N,N-methylenebis(acrylamide) were mixed, and 0.04g of ammonium persulfate was added, and the mixture was reacted at 63°C for 4h, separated, and washed with a mixture of water and methanol, and then dried in an oven at 65°C for 33h, and finally made into powder to obtain modified fly ash;
[0045] (5) 55 g of coal gangue, 2.513 g of PO3, 30 g of fly ash, 8 g of modified fly ash, 6 g of activator (the weight ratio of Na2SiO3, Na2SO4 and NaCl is 1:2:3), and 3 g of naphthalene-based water reducer are mixed and stirred evenly to obtain fly ash gangue cement for coal mines.
[0046] Example 3: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0047] (1) Dispersing fly ash in anhydrous ethanol, stirring evenly, ultrasonically removing impurities for 30 minutes, centrifuging and filtering, dispersing in deionized water, ultrasonically removing impurities for 30 minutes, centrifuging, filtering, and vacuum drying for 24 hours to obtain pretreated fly ash;
[0048] (2) 50 g of pretreated fly ash, 60 ml of hydrogen peroxide (20%) and 60 ml of concentrated sulfuric acid (98%) were mixed and stirred evenly. After the gas was completely released, the mixture was filtered and washed to neutrality, and vacuum dried for 24 hours to obtain hydroxylated fly ash;
[0049] (3) Dispersing 40 g of hydroxylated fly ash in 500 g of anhydrous ethanol, adding formic acid, adjusting the pH to 5, then adding 15 g of KH-570, maintaining at 100 ° C. for 14 h, after the reaction is completed, filtering, washing, and drying to obtain olefinated fly ash;
[0050] (4) at 50°C, 15g of sodium alginate was placed in 300g of deionized water, and after it was completely dissolved, 40g of olefinized fly ash, 25g of polyacrylamide, 3g of trifluoroethyl acrylate and 5g of N,N-methylenebis(acrylamide) were mixed, and 0.05g of ammonium persulfate was added, and the mixture was reacted at 65°C for 4h, separated, and washed with a mixture of water and methanol, and then dried in an oven at 70°C for 36h, and finally made into powder to obtain modified fly ash;
[0051] (5) Mix 60 g of coal gangue, 2.515 g of PO3, 35 g of fly ash, 10 g of modified fly ash, 7 g of activator (the weight ratio of Na2SiO3, Na2SO4 and NaCl is 1:2:3), and 5 g of naphthalene-based water reducer, and stir evenly to obtain fly ash gangue cement for coal mines.
[0052] Comparative Example 1: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0053] (1) Dispersing fly ash in anhydrous ethanol, stirring evenly, ultrasonically removing impurities for 25 minutes, centrifuging and filtering, dispersing in deionized water, ultrasonically removing impurities for 25 minutes, centrifuging, filtering, and vacuum drying for 20 hours to obtain pretreated fly ash;
[0054] (2) 45 g of pretreated fly ash, 55 ml of hydrogen peroxide (20%) and 55 ml of concentrated sulfuric acid (98%) were mixed and stirred evenly. After the gas was completely released, the mixture was filtered and washed to neutrality, and vacuum dried for 20 h to obtain hydroxylated fly ash.
[0055] (3) Disperse 35 g of hydroxylated fly ash in 400 g of anhydrous ethanol, add formic acid, adjust the pH to 4.7, then add 13 g of KH-570, keep at 95 ° C. for 13 h, filter, wash and dry after the reaction is completed to obtain olefinated fly ash;
[0056] (4) 35 g of olefinized fly ash, 23 g of polyacrylamide, 2 g of trifluoroethyl acrylate, 2 g of N,N-methylenebis(acrylamide) and 250 g of deionized water were mixed, and 0.04 g of ammonium persulfate was added, and the mixture was reacted at 63° C. for 4 h, separated, and washed with a mixture of water and methanol, and then dried in an oven at 65° C. for 33 h, and finally powdered to obtain modified fly ash;
[0057] (5) 55 g of coal gangue, 2.513 g of PO3, 30 g of fly ash, 8 g of modified fly ash, 6 g of activator (the weight ratio of Na2SiO3, Na2SO4 and NaCl is 1:2:3), 3 g of naphthalene-based water reducer and 1.38 g of sodium alginate are mixed and stirred evenly to obtain fly ash gangue cement for coal mine.
[0058] Comparative Example 2: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0059] (1) Dispersing fly ash in anhydrous ethanol, stirring evenly, ultrasonically removing impurities for 25 minutes, centrifuging and filtering, dispersing in deionized water, ultrasonically removing impurities for 25 minutes, centrifuging, filtering, and vacuum drying for 20 hours to obtain pretreated fly ash;
[0060] (2) 45 g of pretreated fly ash, 55 ml of hydrogen peroxide (20%) and 55 ml of concentrated sulfuric acid (98%) were mixed and stirred evenly. After the gas was completely released, the mixture was filtered and washed to neutrality, and vacuum dried for 20 h to obtain hydroxylated fly ash.
[0061] (3) Disperse 35 g of hydroxylated fly ash in 400 g of anhydrous ethanol, add formic acid, adjust the pH to 4.7, then add 13 g of KH-570, keep at 95 ° C. for 13 h, filter, wash and dry after the reaction is completed to obtain olefinated fly ash;
[0062] (4) 35 g of olefinized fly ash, 23 g of polyacrylamide, 2 g of trifluoroethyl acrylate, 2 g of N,N-methylenebis(acrylamide) and 250 g of deionized water were mixed, and 0.04 g of ammonium persulfate was added, and the mixture was reacted at 63° C. for 4 h, separated, and washed with a mixture of water and methanol, and then dried in an oven at 65° C. for 33 h, and finally powdered to obtain modified fly ash;
[0063] (5) 55 g of coal gangue, 2.513 g of PO3, 30 g of fly ash, 8 g of modified fly ash, 6 g of activator (the weight ratio of Na2SiO3, Na2SO4 and NaCl is 1:2:3), and 3 g of naphthalene-based water reducer are mixed and stirred evenly to obtain fly ash gangue cement for coal mines.
[0064] Comparative Example 3: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0065] (1) Dispersing fly ash in anhydrous ethanol, stirring evenly, ultrasonically removing impurities for 25 minutes, centrifuging and filtering, dispersing in deionized water, ultrasonically removing impurities for 25 minutes, centrifuging, filtering, and vacuum drying for 20 hours to obtain pretreated fly ash;
[0066] (2) 55 g of coal gangue, 2.513 g of PO3, 30 g of pretreated fly ash, 2.45 g of polyacrylamide, 1.38 g of sodium alginate, 0.21 g of trifluoroethyl acrylate, 6 g of activator (the weight ratio of Na2SiO3, Na2SO4 and NaCl is 1:2:3), and 3 g of naphthalene-based water reducer are mixed and stirred evenly to obtain fly ash gangue cement for coal mines.
[0067] Comparative Example 4: A fly ash gangue cement solid for coal mines, the specific preparation steps are as follows:
[0068] The difference from Example 2 is that trifluoroethyl acrylate is replaced by an equal mass of 1H,1H,2H,2H-perfluorodecyl acrylate, and the remaining steps are the same as Example 2.
[0069] Performance Testing
[0070] The adhesive obtained in the embodiment and the comparative example was mixed with water in a mass percentage of 78%:22% to obtain a slurry, and the performance of the slurry was tested:
[0071] Water bleeding rate: Stir the prepared slurry evenly and pour it into a 500ml beaker and let it stand for 1.5 hours. Use a syringe to suck out the slurry water, read the precipitated water value, and calculate it according to the following formula:
[0072]
[0073] Setting time: The setting time of the filling slurry was tested according to GB / T1346-2011. The test results are shown in Table 1.
[0074] Filling body performance test:
[0075] Compressive strength: According to GB / T 4111-2013, the samples obtained in the embodiments and comparative examples were mixed with water, poured into a blender and stirred for 5 min, and injected into a mold with a specification of 70.7 mm×70.7 mm×70.7. After being cured and left to stand for 24 h indoors, the specimens were taken out of the mold and placed in a constant temperature and humidity curing box (temperature 20°C±2°C, humidity 90%±5%) for curing. The curing was tested for 3 d and 28 d. Three parallel test blocks were prepared for each test and tested using a YAW-3000B strength testing machine. The average value was taken as the final strength. The test results are shown in Table 1.
[0076] Heavy metal solidification performance: According to GB 5085.7-2019 "Hazardous Waste Identification Standard", the leaching toxicity test was carried out on the samples cured for 28 days using the leaching toxin leaching method, sulfuric acid and nitric acid method. In the experiment, concentrated sulfuric acid and concentrated nitric acid were added in a mass ratio of 2:1, and diluted with ordinary water to maintain the pH of the leaching solution at 3.2±0.05. When the leaching time reached 60 days, the leaching solution was filtered and collected through a 0.65μm filter, and the heavy metal leaching concentration was analyzed by inductively coupled plasma mass spectrometry, and compared and evaluated with the national standard. The national standard requires that Cu should not exceed 100μg / ml and Mn should not exceed 5μg / ml.
[0077] Table 1 Performance test results
[0078]
[0079]
[0080] Data Analysis:
[0081] The fly ash gangue cementing material for coal mines of the present invention has good fluidity after being mixed with water to form slurry, is convenient for pipeline transportation, and has a short setting time. The filling blocks obtained by curing the slurry have excellent compressive strength and heavy metal solidification ability.
[0082] It can be seen from Example 2 and Comparative Examples 1 and 2 that the present invention improves the compressive strength and heavy metal solidification performance of the filling block by adding sodium alginate in the process of preparing the modified fly ash. This is mainly because on the one hand, sodium alginate itself has certain adsorption properties and can fix some heavy metal ions. On the other hand, during the grafting process, part of the polyacrylamide and fluorine chains are first grafted to the surface of the sodium alginate microspheres and then grafted to the surface of the fly ash, so that the effective grafting density of the polyacrylamide and fluorine chains is significantly increased, further improving the ability to solidify metal ions. At the same time, the microspheres form a three-dimensional network structure on the surface of the fly ash. This structure not only wraps the fly ash particles and the heavy metal ions adsorbed on their surfaces, but also fills the gaps between the particles, thereby improving the overall density of the material, reducing the migration path of the heavy metal ions, and reducing the possibility of their dissolution and release.
[0083] It can be seen from Example 2 and Comparative Examples 1, 2 and 3 that in the process of preparing modified fly ash, polyacrylamide, sodium alginate and trifluoroethyl acrylate are grafted to the surface of fly ash. Compared with direct mixing, the present invention can be more evenly distributed on the surface of fly ash, ensuring that each particle is effectively protected, thereby improving the immobilization effect of the overall material, not only enhancing the physical barrier effect, but also jointly fixing heavy metal ions through a variety of chemical mechanisms, so that the ability to fix heavy metal ions can be greatly improved, and the uniform distribution makes the overall density of the material improved to a certain extent, thereby improving the compressive strength of the filling body.
[0084] It can be seen from Example 2 and Comparative Example 4 that the present invention adopts modified substances with longer fluorine chains, so that the compressive strength and heavy metal curing performance of the filler are improved to a certain extent. On the one hand, the fluorine chain can enhance the hydrophobicity of the material, thereby reducing the penetration of rainwater and groundwater into the filling block. On the other hand, the longer fluorine side chains can be entangled with each other, so that the compressive strength of the filling block is improved to a certain extent.
[0085] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A fly ash gangue cement for coal mines, characterized in that: The raw materials include the following parts by weight: 50-60 parts of coal gangue, 10-15 parts of cement, 25-35 parts of fly ash, 5-10 parts of modified fly ash, 4-7 parts of activator, and 1-5 parts of water reducing agent; The preparation steps of the modified fly ash are as follows: S1: removing impurities from fly ash to obtain pretreated fly ash; S2: pretreated fly ash, hydrogen peroxide and concentrated sulfuric acid are mixed, stirred evenly, allowed to stand until the gas is completely released, filtered, washed and dried to obtain hydroxylated fly ash; S3: Mix and stir the hydroxylated fly ash and anhydrous ethanol, adjust the pH to 4.5-5, then add silane coupling agent KH-570, react at 90-100° C. for 12-14 hours, filter, wash and dry to obtain olefinated fly ash; S4: Sodium alginate is dissolved in deionized water at 50°C, followed by the addition of olefinated fly ash, polyacrylamide, trifluoroethyl acrylate and N,N-methylenebis(acrylamide), and after ultrasonic homogenization, an initiator is added. After reacting at 60-65°C for 3-4h, the fly ash is separated, washed, dried, crushed and sieved to modify the fly ash.
2. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The coal gangue is composed of coal gangue fine aggregate and coal gangue coarse aggregate in a weight ratio of 1:
1.
3. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The cement is ordinary Portland cement with a PO3 of 2.
5.
4. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The particle size of the fly ash is 10-100 μm.
5. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The activator is a mixture of Na2SiO3, Na2SO4 and NaCl in a weight ratio of 1:2:
3.
6. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The water reducer is one of lignin sulfonate water reducer, naphthalene water reducer, polycarboxylic acid water reducer, melamine water reducer or aminosulfonate water reducer.
7. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The usage ratio of the pretreated fly ash, hydrogen peroxide and concentrated sulfuric acid in step S2 is 40-50g:50-60ml:50-60ml.
8. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The weight ratio of the hydroxylated fly ash, the silane coupling agent KH-570 and the anhydrous ethanol in step S3 is 30-40g:10-15g:300-500g.
9. The fly ash gangue cement for coal mine according to claim 1, characterized in that: The weight ratio of the olefinated fly ash, polyacrylamide, trifluoroethyl acrylate, N,N-methylenebis(acrylamide), sodium alginate, initiator and deionized water in step S4 is 30-40g:20-25g:1-3g:1-5g:10-15g:0.03-0.05g:200-300g.
10. A method for preparing fly ash and gangue cement for coal mines according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are mixed in proportion and stirred evenly to obtain fly ash gangue cement solid for coal mine.
Citation Information
Patent Citations
A coal gangue cemented backfill material and a high-flowability, high-solids-content cemented backfill slurry
CN113321468B
Coal gangue backfilling functional material and preparation method thereof
CN118754517A
Preparation method of cationic surfactant modified fly ash
CN103304175A
Magnetic sewage treatment agent and preparation method thereof
CN109761331A
Preparation method for hydrophobic modified silk fiber material
CN111501341A